Identifying dietary stress in marginal environments: bone fats, optimal foraging theory and the seasonal round - Outram, Alan K (Oxbow Books, 2003)
Reproduced with permission of the publisher. Copyright © Oxbow Books and the individual authors, 2004 The importance of fat in the diet is outlined and the importance of bones as a reliable source of fat is explained. Different patterns of bone marrow and grease exploitation are discussed with particular reference to marginal environments and how levels of exploitation will be related to levels of dietary stress. The possible role of Optimal Foraging Theory in addressing this issue is outlined and adaptations of Marginal Value Theorem and Diet Breadth specific to bone fat exploitation are put forward and described. The methodologies for studying patterns of bone fat exploitation within archaeological assemblages are outlined and four example applications relating to Norse and Pale-Eskimo Greenland, Norse Iceland and Middle Neolithic Gotland are used to illustrate what these methods can show. These case studies are discussed with specific reference to identifying dietary stress in marginal environments and the role of seasonality to this issue.